Maximal elements and equilibria of generalized games for 𝒰-majorized and condensing correspondences - George Xian-Zhi Yuan; E. Tarafdar (International Journal of Mathematics and Mathematical Sciences)
In this paper, we first give an existence theorem of maximal elements for a new type of preference correspondences which are 𝒰-majorized. Then some existence theorems for compact (resp., non-compact) qualitative games and generalized games in which the constraint or preference correspondences are 𝒰-majorized (resp., Ψ-condensing) are obtained in locally convex topological vector spaces.